Shear strength (fall cone) from IODP Hole 386-M0094A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Undrained shear strength data from fall cone testing of the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). This dataset was obtained at the end of the core processing workflow during the third phase (Personal Sampling Party, PSP) of expedition 386, which took place between 2022-11-15 – 2022-11-30 onboard D/V Chikyu. Measurements were performed on the work halves of core sections at an interval of approx. 1 meter using an ELE International fall cone penetrometer (STANDARD BS1377) with the following cone specifications: 35 mm cone, 30 degrees angle, around 30 g, stainless steel, 3.25 (+/-0.05) mm rod diameter. The fall cone penetrometer measures the penetration of a cone as it free falls and embeds itself in the sediment. During testing, the cone (pointing downward) was lowered, so that it just touched the surface of the split core before it was locked in place with the dial gauge reading noted. Undrained shear strength was determined using the empirical formula determined by Hansbo (1957, http://urn.kb.se/resolve?urn=urn:nbn:se:swedgeo:diva-356). The formula of Hansbo (1957) may be inadequate for silty sediment (present in some Expedition 386 cores); therefore, fall cone measurements were obtained preferably in clay-dominated intervals. In three cases (386-M0081B-1H-21,25.5; 386-M0088D-1H-7,25.5; 386-M0091B-1H-10,25.5), data collection was not successful for different reasons (IT problems, human failure). For the sake of completeness, however, the "Sample labels" were nevertheless noted and results left empty. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023